Use of chimerism analysis after allogeneic stem cell transplantation: Belgian guidelines and review of the current literature. Issue 6 (2nd November 2021) - Delie, Anke; Verlinden, Anke; Beel, Karolien; Deeren, Dries; Mazure, Dominiek; Baron, Frédéric; Breems, Dimitri; De Becker, Ann; Graux, Carlos; Lewalle, Philippe; Maertens, Johan; Poire, Xavier; et al.
ABSTRACT: Background: Allogeneic hematopoietic stem cell transplantation (HSCT) is a curative treatment option in both adult and pediatric patients with malignant and non-malignant hematological diseases.  Chimerism analysis, which determines the donor or recipient origin of hematopoietic cells in HSCT recipients, is an essential aspect of post-HSCT follow-up.Objectives: To review the current literature and develop Belgian consensus guidelines for the use of chimerism analysis in the standard of care after allogeneic HSCT.Methods : Non-systematic review of the literature in consultancy with the members of the BHS transplantation committee.Results : Clinical application with regards to prediction of graft failure or relapse as well as cell source are reviewed. A consensus guideline on the use of chimerism analysis after HSCT is presented.Conclusion : Monitoring of the dynamics or kinetics of a patient's chimerism status by serial analysis at fixed time points, as well as on suspicion of relapse or graft failure, is needed to monitor engraftment levels, as well as disease control and possible relapse.